Psychoanalytical analysis of the female character in the novel "Heart of steel" based on the views of Karen Horney - Rouholah Khadivpour; Sareh Zirak; Abdolhosein Farzad; Reza Ghorban jahromi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Karen Horney (1885-1952) is among psychoanalysts who have emphasized on social interactions as effective elements in the making of one's personality and has called on psychoanalysts to scrutinize the social backgrounds in which the individual has grown up. Similarly, we have analyzed and studied "Afsaneh" the main character in the novel "Heart of steel" based on Karen's views. Our descriptive analytical method has aimed to find out which neurociticism has Afsaneh been using to counter her basic anxiety. The study has found that The key to understanding and recognizing the anxiety of the Afsaneh is to understand the patriarchal system in which she is forced to live. In the proper context provided by the patriarchal system, the violent father and the gambling wife of the legend consider themselves justified in humiliating and harassing him, which causes fundamental anxiety in his character. Afsaneh's anxiety increases after immigrating to Tehran and after proving his worth to his father. Therefore, to deal with it, she uses the neurotic tendency of moving against people, but this mechanism is in conflict with the tendencies of moving toward people and moving away from people and causes the formation of a basic conflict in her personality.